Daya Simpan Benih Tomat (Lycopersicum esculentum mill.) Hasil Beberapa Teknik Ekstraksi - I NYOMAN RAGANATHA; I GUSTI NGURAH RAKA; I GEDE KETUT SIADI (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2014)
AbstractTomato Seed (Lycopersicum esculentum Mill.) Storability of Some Extraction Techniques Results                 Shelf life tomato seeds produced by different seed extraction techniques studied using completely randomized design ( CRD ) with three treatments of seed extraction technique and nine replicates. Three seed extraction techniques used are: extraction technique with 2 % HCl, washed with water extraction techniques, and extraction techniques with immersion in water for 24 hours. The seeds are dried until the moisture content ranges from 5 %, then stored at room temperature. Observations before storage include: seed moisture content, the amount of seed moisture content of 5 % per 5 g of seeds, seed purity, germination and speed of germination. Observations during storage include: seed moisture content,  germination and speed of germination. The results showed that the extraction technique of soaking seeds with 2 % HCl able to produce seeds with the lowest percentage of impurities so that the absorption of moisture during the storage period was also the lowest. Extraction technique of soaking seeds with 2 % HCl able to maintain the viability of the seed germination above 80 % until the 12 -week storage period at speeds high enough to germinate. While the seeds of other extraction techniques which have a shorter shelf life. Further research on the storage technique that is able to maintain the viability and vigor of tomato seeds for a longer shelf life.   Key words : Tomato seeds, extraction, seed storage, viability, vigor